Hidden drifts in turbulence. (7th January 2019) - Vlad, M.; Spineanu, F.
Abstract: The paper defines and discusses the concept of hidden drifts in two-dimensional turbulence. These are ordered components of the trajectories that average to zero and do not produce direct transport. Their effects appear in the evolution of the turbulence as a special type of fluxes, which consist of average motion of positive and negative fluctuations in opposite directions. We show that these fluxes have important nonlinear effects in turbulent fluids and in confined plasmas. In the first case, they determine the increase of the large-scale vorticity and velocity at the expense of the small-scale fluctuations by a process of separation of the vorticity fluctuations according to their sign. In the second case, they provide a mechanism for zonal flow generation and a vorticity flux that influences the sheared rotation of the plasma.